METHODOLOGICAL CONTENT OF DEVELOPING SOCIO-CULTURAL COMPETENCE IN FUTURE TEACHERS BASED ON THE SUBJECT OF "ETHNOCULTURE" (Scientific journal of the Fergana State University, 2026)
The article studies the theoretical and methodological foundations of the development of socio-cultural competence in future teachers, the technological foundations of the development of socio-cultural competence in future teachers based on the subject of "Ethnoculture", the effectiveness of the development of socio-cultural competence in future teachers. The methodological content of the development of socio-cultural competence in future teachers based on the subject of "Ethnoculture" is also analyzed.